Preoperative Axillary Lymph Node Evaluation in Breast Cancer: Current Issues and Literature Review. Issue 1 (March 2017) - Choi, Hee Young; Park, Minho; Seo, Mirinae; Song, Eunjee; Shin, So Youn; Sohn, Yu-Mee
Abstract : Abstract: Axillary lymph node (ALN) status is an important prognostic factor for overall breast cancer survival. In current clinical practice, ALN status is evaluated before surgery via multimodal imaging and physical examination. Mammography is typically suboptimal for complete ALN evaluation. Currently, ultrasonography is widely used to evaluate ALN status; nonetheless, results may vary according to operator. Ultrasonography is the primary imaging modality for evaluating ALN status. Other imaging modalities including contrast-enhanced magnetic resonance imaging, computed tomography, and positron emission tomography/computed tomography can play additional roles in axillary nodal staging. The purpose of this article is (1) to review the strengths and weaknesses of current imaging modalities for nodal staging in breast cancer patients and (2) to discuss updated guidelines for ALN management with regard to preoperative ALN imaging.